Efficacy of mycophenolate mofetil as a remission induction therapy in antineutrophil cytoplasmic antibody-associated vasculitis—a meta-analysis - Atsushi Kumanogoh; Kentaro Kuzuya; Takayoshi Morita (RMD Open)
Objectives A few studies on antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) treatments have shown the therapeutic efficacy of mycophenolate mofetil (MMF). However, the therapeutic efficacy of MMF compared with that of cyclophosphamide (CYC) in patients with AAV has not been established. We conducted a systematic review and meta-analysis to assess the efficacy of MMF as a remission induction therapy in patients with AAV comparing it with the efficacy of CYC.Methods We searched randomised controlled trials (RCTs) comparing the efficacy of MMF with that of CYC in patients with AAV on three different websites: PubMed, Cochrane Library and Google Scholar. We compared the difference in the relative risk (RR) of each outcome based on a Mantel-Haenszel random-effects model.Results We analysed data from four RCTs with 300 patients for the study. The 6-month remission rate (RR 1.09, 95% CI 0.86 to 1.38, p=0.48), the 6-month ANCA negativity (RR 1.31, 95% CI 0.91 to 1.90, p=0.15) and the long-term relapse rate (RR 1.36, 95% CI 0.80 to 2.31, p=0.26) were all similar between the two treatments. The rates of death, infection and leucopenia were also similar between the two groups (RR 1.05, 95% CI 0.40 to 2.74, p=0.93; RR 1.26, 95% CI 0.79 to 2.01, p=0.33; RR 0.45, 95% CI 0.16 to 1.32, p=0.15, respectively).Conclusions We found no difference between the therapeutic efficacy of MMF and that of CYC in patients with AAV. MMF may be an alternative remission induction therapy in patients with non-life-threatening AAV.